2010
DOI: 10.1007/s10616-010-9290-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of foam cell formation in cultured macrophages: an improved method with Oil Red O staining and DiI-oxLDL uptake

Abstract: Macrophage-derived foam cell formation elicited by oxidized low-density lipoprotein (oxLDL) is the hallmark of early atherogenesis. Detection of foam cell formation is conventionally practiced by Oil Red O (ORO) staining of lipid-laden macrophages. Other methods include 1,1'-dioctadecyl-3,3,3'3'-tetra-methylindocyanide percholorate (DiI)-labeled oxLDL (DiI-oxLDL) uptake and Nile Red staining. The purpose of the present study is to report an optimized method for assessing foam cell formation in cultured macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 32 publications
(39 reference statements)
2
109
0
2
Order By: Relevance
“…These results indicated that the RPT-heLDL conjugate had entered the cells successfully. The scavenger receptor-mediated uptake of chemically modified lipoproteins by macrophages, including oxidized and acetylated LDL, was found to be concentration dependent ( Xu et al, 2010). Our oil red O-staining results revealed a similar pattern to that of the uptake of RPT-heLDL by U937 macrophage, which also correlated well with the concentration.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These results indicated that the RPT-heLDL conjugate had entered the cells successfully. The scavenger receptor-mediated uptake of chemically modified lipoproteins by macrophages, including oxidized and acetylated LDL, was found to be concentration dependent ( Xu et al, 2010). Our oil red O-staining results revealed a similar pattern to that of the uptake of RPT-heLDL by U937 macrophage, which also correlated well with the concentration.…”
Section: Discussionsupporting
confidence: 70%
“…human THP-1, human monocyte-derived macrophages and murine macrophage cell lines) (Scholz et al, 2004;Moore & Freeman, 2006;Xu et al, 2010). The results of the current study revealed that the FITClabeled protein successfully entered the cell and that oil red O-stained lipid droplets were well distributed throughout the cytosol of the U937 macrophages.…”
Section: Discussionmentioning
confidence: 51%
“…At the time of protein extraction, both cells transfected with ARIA-FLAG or empty vector were nearly confluent, and no significant difference of confluency was detected between the groups. Murine peritoneal macrophages (PMs) were prepared as described previously (22). Briefly, thioglycolate (2 ml of 3% solution in water) was intraperitoneally injected in age-and sex-matched WT and ARIA-deficient mice.…”
Section: Methodsmentioning
confidence: 99%
“…Foam Cell Formation-Foam cell formation was performed as described previously (22,23). Briefly, macrophages were cultured on chamber slides at a density of 5.…”
Section: Methodsmentioning
confidence: 99%
“…Cells that have been plated on cover glassbottom dishes or cytospun can be analyzed for shape to help determine their phenotype, though this can also be per formed on an imaging flow cytometer (Majka et al, 2012). Sorted cells can also be used for in vitro functional assays like antigen presentation (Choi et al, 2009), cytokine production by cytometric bead array (Morgan et al, 2004), phagocytosis (Xu et al, 2010), efferocytosis of apoptotic cells (Friggeri et al, 2010), and killing of pathogens (Drevets et al, 2015).…”
Section: Combining With Other Techniquesmentioning
confidence: 99%